Effects of supplemental degradable intake protein on intake and digestibility of forage sorghum hay - C.P. Mathis; R.C. Cochran; B.C. Woods; J.S. Heldt; Gerald L. Stokka; E.S. Vanzant; K. C. Olson; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1997)
Sixteen ruminally fistulated beef steers with ad libitum access to forage sorghum hay were used to evaluate the effect of increasing level of degradable intake protein (DIP) on forage intake and digestion. Forage OM intake and total OM intake were enhanced with increasing level of DIP supplementation. Similarly, increases in total OM digestibility and total digestible OM intake (TDOMI) were evident. Compared with the negative control, TDOMI was approximately doubled at the highest level of DIP supplementation.
Keywords: Cattlemen& #x27; s Day; 1997; Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 783; Beef; Steers; Forage; Intake; Digestion; Degradable intake protein